Overexpression of tomato thioredoxin h (SlTrxh) enhances excess nitrate stress tolerance in transgenic tobacco interacting with SlPrx protein - Zhai, Jiali (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2021 Elsevier B.V. All rights reserved.